2010
DOI: 10.1021/jf102554h
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Reduction Leading to Cell Wall Rupture Is More Important for the β-Carotene Bioaccessibility of Raw Compared to Thermally Processed Carrots

Abstract: The amount of nutrients that can be released from food products (i.e., nutrient in vitro bioaccessibility) is often studied as it is a starting point for investigating nutrient bioavailability, an indicator for the nutritional value of food products. However, the importance of mastication as a particle size reduction technique is poorly understood and is often neglected during in vitro procedures determining bioaccessibility. Therefore, the aim of the present work was to study the effect of mechanical breakdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 31 publications
8
99
0
2
Order By: Relevance
“…To the best of our knowledge, evidence from human trials for this observation is lacking. In agreement with Lemmens et al (2010), Netzel et al (2011) reported the highest release of carotenes from cooked carrots when compared …”
Section: Foods With Crystalloid Chromoplastssupporting
confidence: 89%
See 1 more Smart Citation
“…To the best of our knowledge, evidence from human trials for this observation is lacking. In agreement with Lemmens et al (2010), Netzel et al (2011) reported the highest release of carotenes from cooked carrots when compared …”
Section: Foods With Crystalloid Chromoplastssupporting
confidence: 89%
“…For example, Lemmens et al (2010) showed a strong positive correlation of a more intense mastication with an enhanced in vitro carotenoid bioaccessibility from raw, fresh carrots. After rigorous cooking of the carrots, the specific dependency of β-carotene bioaccessibility on mastication of the carrot tissue disappeared.…”
Section: Foods With Crystalloid Chromoplastsmentioning
confidence: 91%
“…The particle size obtained during chewing has been studied to understand the effect of the particle size on nutrient release during the later steps in digestion. Similar effects have been reported for other type of nutrients such as β-carotene, as demonstrated by the study performed by Lemmens et al (2010), who evaluated the effect of the particle size on β-carotene bioaccessibility from raw and thermally processed carrots. This situation was clearly observed in rice where in vitro digestion of whole and chewed rice resulted in significant differences in the glucose release rate, with a lower glucose release for whole grain and a higher release when the particle size was smaller than 1000 μm.…”
Section: Chewing As the Starting Point Of Digestionsupporting
confidence: 79%
“…The residue, containing the released carotenoids, is dissolved in a mobile phase solvent (consisting of methanol, methyl-t-butyl ether, and water) and filtered through a 0.45 μm pore size cellulose membrane filter and subjected to reverse phase HPLC. This method has been used after minor modifications to study the effects of thermal processing (Lemmens et al, 2011) and particle size (Lemmens et al, 2010) on β-carotene bioaccessibility from carrots.…”
Section: Applications Of In Vitro Methods and Recommendationsmentioning
confidence: 99%